Developing Speaking and Listening Skills of ESL learners through Use of English Language Movies or Broadcast - Mallesh, N. (International Journal of Psychosocial Rehabilitation, 2021)
Many English as a Second Language (ESL) teachers who are non-native speakers of English have to overcome numerous obstacles to improving their students’ language abilities, especially when developing speaking and listening skills. More and more innovative approaches are essential for them to address these problems. This research is aimed at investigating the use of English language movies in developing the oral and listening skills of student teachers of English. Approximately 600 English-language films are released all over the world in each year, and teachers can utilize them as authentic materials for ESL learners who may find audio and printed materials less motivating. By using student teachers as the participants, the researcher explores how language fluency, pronunciations, vocabulary, and knowledge of colloquial expressions can be enhanced by watching English movies on a regular basis. The study also examines whether the use of English movies for ESL learning can create more opportunities to learn language usage in real life while creating an autonomous learning environment. Furthermore, it explores the possibility of learning words and phrases in informal situations that are not taught in ESL classrooms. Living in an English-speaking country is considered the easiest way to learn English. Watching movies on a regular basis may provide the same experience for ESL learners to develop the speaking and listening skills of English language.